A mechanical model of composite floor systems under an internal column removal scenario. (15th November 2018) - Fu, Qiu Ni; Tan, Kang Hai; Zhou, Xu Hong; Yang, Bo
Highlights: A model is proposed to estimate the responses of composite floors under internal column loss. The model can accurately predict push-down load–displacement curves. The model can capture the effects of key parameters. The procedure of the model can be implemented by a spreadsheet method. Abstract: This is the first time that a mechanical model is proposed to estimate the entire load–deflection response of three-dimensional (3D) steel-frame-composite-slab systems (composite floors) subjected to internal column loss. The model incorporates three branches to capture the response at small deformation, transitional and large deformation stages. For ease of hand calculations, the load carried by a 3D composite floor is assumed to be the summation of the respective contributions from the composite slabs and the steel sub-frame. At small deformation stage, the load is resisted through flexural action. But at large deformation stage, structural capacity is mostly contributed by membrane action in the slabs and catenary action in the steel beams. The assumptions and failure criteria in the last stage are based on the results of actual experimental tests. The derivations are discussed in detail, followed by verifications of the model. Compared with actual test results and numerical simulations, the model shows reasonable accuracy in predicting load–displacement curves of 3D composite floor systems under an internal column removal scenario. Besides this novelty and distinct feature from other studies, the model can capture the effects of key parameters, such as slab aspect ratio, joint type, number of joint bolts, slab thickness, reinforcement ratio in the slab and thickness of steel decking. Most importantly, the procedure of the model can be implemented by a spreadsheet method, which provides a simple and numerical robust tool for engineers to calculate progressive collapse resistance of structures for a missing column scenario.